Low back pain and its determinants among wait staff in Gondar town, North West Ethiopia: A cross-sectional study - Yalew, Ermias Solomon; Adem, Kedir Sany; Kibret, Alemu Kassaw; Gashaw, Moges (Frontiers in Pain Research, 2022)
Background: Low back pain is a common public health issue in the working population and one of a leading cause of disability. It is the leading cause of work-related conditions and the most common reason for filing a workers' compensation claim in low and middle income countries. Ethiopia is a developing country, there is a shortage of working materials, skilled labor, and a lack of awareness of ergonomics posture, which leads to lifting heavy objects, long periods of standing, repetitive twisting, and sustained one posture for long periods of time without a shift. As a result, this study was to assess the prevalence and associated factors of work-related low back pain among restaurant wait staff in Gondar, Ethiopia, in the year 2019. Methods: institution-based cross-sectional study including 420 restaurant wait personnel was undertaken from March 1 to April 30, 2019. Simple random sampling procedure was used to choose the restaurants and wait staff. A standardized Nordic questionnaire was used to collect data. Data was entered in to Epi Info7 and analyzed in SPSS version 20. Uni-variable analysis and multivariable logistic regression analysis were computed. The significance of associations was reported by a P value <0.05 and adjusted odds ratio (AOR). Result: a total of 420 participants (99.53% response rate) ranging in age from 17 to 53 years old participate, with 184 (43.8%) reporting low back pain at some point of the past 12 months. Females had a higher prevalence of 130. (70.6%). Sex [AOR=2.98; 95% CI: 1.07-8.30], frequent exercise [AOR 0.47; 95% CI 0.24, 0.93], extended standing [AOR 8.82 CI: 95% 3.30, 20.32], and repetitive tasks [AOR 7.49 CI: 95% 4.29, 13.19] were all found to be significant predictors. Conclusion: More than two-fifth of waitresses and waiters reported low back discomfort at some point of the past 12 months. being female, standing for lengthy periods of time while serving, and performing repetitive tasks were predisposing factors . Regular exercise was found to be a protective factor against low back pain in wait staff. Delivering ongoing safety training is among the most potent essential measures required in preventing low back pain.